EUFEMISME DAN DISFEMISME DALAM NOVEL BURUNG-BURUNG MANYAR KARYA YUSUF BILYARTA MANGUNWIJAYA (EUPHEMISM AND DISPHEMISM IN YUSUF BILYARTA MANGUNWIJAYA’S NOVEL BURUNG-BURUNG MANYAR) - Dina Ayesha Fahria (Universitas Lambung Mangkurat, 2022)
Euphemism and Disphemism in the Yusuf Bilyarta Mangunwijaya’s Novel Burung-Burung Manyar. This study aims to describe linguistic forms and functions of the use of euphemisms and dysfemisms in Y.B.'s Burung-Burung Manyar novel Mangunwijaya. The description is done by qualitative descriptive using data in the form of words, sentences or images instead of numbers. This study uses data collection techniques with careful reading and note-taking techniques to find data to interpret language forms and functions of using euphemisms and dysfemisms. Based on the analysis, the results show that the forms of euphemism and dysfemism used in Y.B.Mangunwijaya's novelBurung-Burung Manyar are in the form of words, phrases and expressions. When viewed from the type of function found euphemisms, namely as a tool to smooth speech, as a tool to keep something secret, as a tool for diplomacy, as an educational tool and as a tool to repel danger. Furthermore, when viewed from the type of dysphemic function found, namely as an expression of anger or annoyance, expression of disappointment, disclosure of fear, expression of pity, and expression of disgust and dirty.Key words: euphemism, dysfemism, novel, functions, formsEufemisme dan Disfemisme dalam Novel Burung-Burung Manyar karya Yusuf Bilyarta Mangunwijaya. Penelitian ini bertujuan untuk mendeskripsikan bentuk kebahasaan dan fungsi penggunaan eufemisme dan disfemisme dalam novel Burung-Burung Manyar karya Y.B. Mangunwijaya. Deskripsi tersebut dilakukan dengan deskriptif kualitatif yang menggunakan data berupa kata, kalimat, atau gambar dan bukan angka. Penelitian ini menggunakan Teknik pengumpulan data dengan teknik baca dan teknik catat secara teliti untuk menemukan data untuk diinterpretasi bentuk kebahasaan dan fungsi penggunaan eufemisme dan disfemisme. Berdasarkan hasil analisis, Hasil penelitian menunjukkan bahwa bentuk kebahasaan eufemisme dan disfemisme yang digunakan dalam novel Burung-Burung Manyar karya Y.B.Mangunwijaya berupa kata, frasa dan ungkapan. Jika dilihat dari jenis fungsi eufemisme yang ditemukan yaitu sebagai alat untuk menghaluskan ucapan, sebagai alat untuk merahasiakan sesuatu, sebagai alat untuk berdiplomasi, sebagai alat pendidikan dan sebagai alat penolak bahaya. Selanjutnya, apabila dilihat dari jenis fungsi disfemisme yang ditemukan yaitu sebagai pengungkapan rasa marah atau kesal, pengungkapan rasa kecewa, penguungkapkan rasa takut, pengungkapan rasa kasihan, dan pengungkapan rasa jijik dan kotor.Kata-kata Kunci: eufemisme, disfemisme, novel, fungsi, bentuk